Design of Automatic Coffee and Milk-Making Machine Based on Arduino - Sujono, Sujono; Sihab, Riski; Yaqin, Nurul (SAINTEKBU, 2023)
Coffee is a popular drink all over the world and comes from the seeds of the coffee plant. The coffee production process includes several stages, such as harvesting, processing, grinding, and roasting. Each stage affects the quality and taste of the coffee produced. This machine is designed to use 2 Arduino Unos as controllers with I2C communication. The purpose of this research is to design and conduct trials on the process of making Arduino-based automatic coffee drink machines. the method in this study uses the waterfall method which includes analysis, design, coding and testing. The machine testing stage is carried out on the servo to measure coffee, milk and sugar, the tool test is also carried out on an electric heater to adjust the water temperature. sugar 3.2 - 3.7 grams, bitter coffee measures between 5.2 - 5.8 coffee with a sugar ratio of 3.0 - 4.0 grams, moderate coffee measures between 2.3 - 2.7 with a sugar ratio of 2, 0 – 2.4 grams, Milk measures between 5.1 – 5.8 gram with sugar ratio between 3.1 – 3.5 gram and coffee milk measure with ratio 4.2 – 4.8 for a coffee measure, 3.2 -3.3 grams for the sugar measure and 3.2 – 3.3 grams for the milk measure